5(3x+7)=-19+39

Simple and best practice solution for 5(3x+7)=-19+39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3x+7)=-19+39 equation:


Simplifying
5(3x + 7) = -19 + 39

Reorder the terms:
5(7 + 3x) = -19 + 39
(7 * 5 + 3x * 5) = -19 + 39
(35 + 15x) = -19 + 39

Combine like terms: -19 + 39 = 20
35 + 15x = 20

Solving
35 + 15x = 20

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-35' to each side of the equation.
35 + -35 + 15x = 20 + -35

Combine like terms: 35 + -35 = 0
0 + 15x = 20 + -35
15x = 20 + -35

Combine like terms: 20 + -35 = -15
15x = -15

Divide each side by '15'.
x = -1

Simplifying
x = -1

See similar equations:

| 17+p=30 | | 4+5lnx=19 | | 5u^3+4u^2-25u-20=0 | | 5(5x+2)-5= | | 4(-6x-2)+10=8(-3x-1)+14 | | n/-20=0 | | -4(15y+1)+8=20(-3y+5)-102 | | -344=8(8v-3) | | (X^3-7)/(x-2) | | 18x=288 | | 1(-4x-5)+7=4(-1x-4)+18 | | x+5=8+x | | s^2=323 | | 3+3x=3x+2 | | 3/4(2?3M)=24 | | 26/y=2 | | -147=3k-3(8k+7) | | -1(x+3)-3=-6(x+8) | | 5(x/5)-3(5)=5(x/5) | | 10=-7-3x | | -6z-9(-8z-4)=2-5(-9-z) | | 5(1-2x)+8=15 | | 6(x-3)-2(x-2)=1 | | 23=33-2(4-2w) | | 12/11•5/8 | | 12/8•5/8 | | 7(3x-2)=-39 | | -9x+3=-8x | | 9x+8=-1x-13 | | 3+.20y=2x+4 | | (n+18)+2n=90 | | -23=2x+3x+2 |

Equations solver categories